Investigation of the underlying, modifiable and non-modifiable risk factors for gestational diabetes among women living in Cape Town - Koech, Elzie (Department of Human Biology, 2024)
Gestational Diabetes Mellitus has adverse effects in pregnancy that affects both the mother and infant. These complications include preeclampsia, macrosomia, preterm birth and risk of developing type 2 diabetes later in life. Understanding the risk factors for GDM is important in order to come up with intervention programs. This study aimed to determine the underlying modifiable, non-modifiable and intermediate risk factors of GDM for women living in Cape Town South Africa. We also compared lifestyle factors between women after diagnosis of GDM and women without GDM. Methods: We conducted a case control study among women living in Cape Town. Cases were defined as women diagnosed with GDM recruited at Groote Schuur Hospital while controls were women without GDM recruited from Vanguard clinic. Questionnaires and medical record review were used to collect data. The association between GDM and both risk factors and lifestyle variables was analysed using multivariable logistic regressions, with GDM as a binary outcome variable. Results: A total of 167 cases and 199 controls were included in the study. The mean age of cases was 32.5 years (28.0-37.0) and the mean age of controls was 25 years (22.0-31.0). In adjusted analyses, the risk factors for GDM were; family history of diabetes mellitus (OR 3.10, 95% CI 1.45-6.61, p =003), (MUAC) (OR 1.17, 95% CI 1.04-1.31, p =0.008) and stillbirth (OR 11.61, 95% CI 1.04-129.90, p =0.047), and BMI (OR 1.11, 95% CI 1.05-1.17, p